2010
DOI: 10.1111/j.1365-2869.2010.00891.x
|View full text |Cite
|
Sign up to set email alerts
|

Slow eye movement detection can prevent sleep-related accidents effectively in a simulated driving task

Abstract: SUMMARY A delayed response caused by sleepiness can result in severe car accidents. Previous studies suggest that slow eye movement (SEM) is a sleep-onset index related to delayed response. This study was undertaken to verify that SEM detection is effective for preventing sleep-related accidents. We propose a real-time detection algorithm of SEM based on feature-extracted parameters of electrooculogram (EOG), i.e. amplitude and mean velocity of eye movement. In Experiment 1, 12 participants (33.5 ± 7.3 years) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…In addition, Åkersted and Gillberg (1990) demonstrated that the changes of SEM with eyes open did not occur until the subjective perceptions of sleepiness fell between "sleepy" and "extremely sleepy-fighting sleep" (KSS≥ 7). SEM detection is apparently an effective method for preventing sleepiness-related accidents by falling asleep, as shown in a study by Shin et al (2011).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In addition, Åkersted and Gillberg (1990) demonstrated that the changes of SEM with eyes open did not occur until the subjective perceptions of sleepiness fell between "sleepy" and "extremely sleepy-fighting sleep" (KSS≥ 7). SEM detection is apparently an effective method for preventing sleepiness-related accidents by falling asleep, as shown in a study by Shin et al (2011).…”
Section: Discussionmentioning
confidence: 93%
“…Because ocular variables (e.g., pupils, eye movement, and blinking) change depending on the level of sleepiness and because they can be measured without contact or restraint, several researchers have investigated methods for measuring drivers' sleepiness using ocular variables (Åkerstedt et al, 2010;Dinges et al, 1998;Johns et al, 2007;Shin et al, 2011;Ueno et al, 2007). Studies using a sleep deprivation protocol have demonstrated that participants show a decrease in the peak velocity of saccadic eye movement (De Gennaro et al, 2000) and relative peak velocity of closing or reopening of blink , an increase of the percentage of time in each minute occupied by slow eye movement (SEM) (Åkerstedt and Gillberg, 1990) and by eyelid closure (percentage of eyelid closure time over the pupil per certain period: PERCLOS) (Dinges et al, 1998;Wierwille and Ellsworth, 1994), increase (Barbato et al, 2007) or decrease (De Gennaro et al, 2005) of blink frequency, prolonged eyelid closure time during blink and total blink duration , and smaller pupil size (Wilhelm et al, 1998) after or during sleep deprivation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…If a target is moving quickly across the entire field of vision, pursuit is often accompanied by a saccade to catch up with the target. Some authors claim that it is desirable to analyze slow eye movements to evaluate the state of a driver's activity [15]. Vergence eye movements occur when the eyes are guided to the centre of the field of view to focus on a near object.…”
Section: Types Of Eye Movementsmentioning
confidence: 99%